Shocks, Stocks, and Socks: Smoothing Consumption over a Temporary Income Loss. - Browning, M; Crossley, T (MIT Press, 2009)
We investigate how households in temporarily straitened circumstances due to an unemployment spell cut back on expenditures and how they spend marginal dollars of unemployment insurance (UI) benefit. Our theoretical and empirical analyses emphasize the importance of allowing for the fact that households buy durable as well as non-durable goods. The theoretical analysis shows that in the short run households can cut back significantly on total expenditures without a significant fall in welfare if they concentrate their budget reductions on durables. We then present an empirical analysis based on a Canadian survey of workers who experienced a job separation. Exploiting changes in the unemployment insurance system over our sample period we show that cuts in UI benefits lead to reductions in total expenditure with a stronger impact on clothing than on food expenditures. Our empirical strategy allows that these expenditures may be non-separable from employment status. The effects we find are particularly strong for households with no liquid assets before the spell started. These qualitative findings are in precise agreement with the theoretical predictions.